The Role of COVID-19 in Antibiotic Resistance in Pediatric Population - Kirill O. Kuznetsov; Laysan R. Tukbaeva; Valeriya V. Kazakova; Kamilla R. Mirzoeva; Ekaterina A. Bogomolova; Adelina I. Salakhutdinova; Darya Yu. Ponomareva; Aigul R. Garipova; Marina S.-M. Mutsolgova; Arslan G. Galimkhanov; Marsel I. Sakhibgareev; Elina R. Guzhvieva (Union of pediatricians of Russia, 2023)
There is data on the irrational use of antimicrobial drugs in pediatric population during the COVID-19 pandemic. This could lead to potential development of antibiotic resistance and increased morbidity and mortality among this vulnerable population group. The aim of this review is to study the role of COVID-19 in antimicrobial drugs administration and antibiotic resistance development, as well as to determine a set of measures for its prevention. Recent studies results have shown that COVID-19 pandemic had both direct and indirect impact on antibiotic resistance development in pediatric population. The COVID-19 outbreak has revealed weaknesses in health systems around the world. Antibiotics administration in patients with coronavirus infection during this period exceeded the number of cases with bacterial co-infection or other diseases. Thus, it indicates irrational antibiotic treatment. There were cases of inappropriate antibiotics administration during the crisis caused by the COVID-19 pandemic even in regions with long-term rational antibiotic treatment programs. One of the most viable methods to combat antibiotic resistance is to improve approaches in health care and to increase preparedness to infectious outbreaks. Increasing clinical competence of medical workers, accessibility of medical facilities, permanent supply of high-quality and cheap antibiotics, vaccines, reducing COVID-19 testing time, and adequate administration of antibacterial agents are the measures that can prevent diseases caused by drug resistance. All stakeholders (health authorities, regulating authorities, politicians, scientific community, pharmaceutical companies) have to collaborate and achieve results to implement all the mentioned above protection measures.